Non-CpG Oligonucleotides Exert Adjuvant Effects by Enhancing Cognate B Cell-T Cell Interactions, Leading to B Cell Activation, Differentiation, and Isotype Switching - Melinda Herbáth; Krisztián Papp; Anna Erdei; József Prechl (Journal of Immunology Research, 2015)
Natural and synthetic nucleic acids are known to exert immunomodulatory properties. Notably, nucleic acids are known to modulate immune function via several different pathways and various cell types, necessitating a complex interpretation of their effects. In this study we set out to compare the effects of a CpG motif containing oligodeoxynucleotide (ODN) with those of a control and an inhibitory non-CpG ODN during cognate B cell-T cell interactions. We employed an antigen presentation system using splenocytes from TCR transgenic DO11.10 mice and the ovalbumin peptide recognized by the TCR as model antigen. We followed early activation events by measuring CD69 expression, late activation by MHC class II expression, cell division and antibody production of switched, and nonswitched isotypes. We found that both of the tested non-CpG ODN exerted significant immunomodulatory effects on early T cell and on late B cell activation events. Importantly, a synergism between non-CpG effects and T cell help acting on B cells was observed, resulting in enhanced IgG production following cognate T cell-B cell interactions. We propose that non-CpG ODN may perform as better adjuvants when a strong antigen-independent immune activation, elicited by CpG ODNs, is undesirable.